Symbolic Convergence in A Social Movement: A Case of “Pengumpulan Satu Juta Ktp” by Teman Ahok - Mia Angeline (Bina Nusantara University, 2016)
Internet plays an important role in modern social movements. One of the modern social movements succeeded in Jakarta was initiated by Teman Ahok named